Kardiochirurgia wad wrodzonych Fontan procedure: influence of single ventricle morphology on early and late results - Kołcz, Jacek; Januszewska, Katarzyna; Malec, Edward (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2006)
Introduction: The single, morphologically right ventricle (SV) is considered to be a risk factor of the Fontan circulation. Recent modifications of the Norwood and Fontan operations (FO) significantly increased the number of such patients. Aim: The purpose of this study was to evaluate the influence of SV morphology on the results of the staged approach. Material and methods: Between 1990 and 2005, 270 patients with SV underwent staged FO. There were 130 (48.6%) children with left ventricular (group I) and 140 (51.8%) with right ventricular (group II) morphology. All patients underwent initial palliative surgery followed by hemi-Fontan and fenestrated FO. Retrospective comparative analysis of the perioperative and follow-up data (including echocardiography, cardiac catheterisation and exercise test) was carried out. Results: Overall mortality was 10.4%; 12 (4.4%) patients died after hemi-Fontan and 16 (6.2%) after FO. There was no difference in mortality rate between groups. After the hemi-Fontan and Fontan procedures the end-diastolic ventricular pressure and cardiac index were significantly increased in group II. After the Fontan procedure the pulmonary artery pressure and central venous pressure were significantly increased in group II. There were no differences in the incidence of pleural effusions. Children with single right ventricle had longer duration of the pleural effusions (p<0.001). In cardiorespiratory response there was a higher anaerobic threshold (p=0.017) and peak fraction of the death space (p=0.041) in group II. Fifteen patients (6.2%) were in NYHA class III, the others in NYHA class II or I. There was no difference in NYHA classification between groups. Conclusions: Staged FO is associated with low mortality and morbidity regardless of ventricular morphology. Although RV was a risk factor for prolonged pleural drainage correlated with elevated VEDP, PAP and CVP, its performance and response to exercise were comparable to LV.